KEBIJAKAN POLITIK PENDIDIKAN DALAM PEMBANGUNAN MORALSOSIAL - Moh. Afiful hair (Universitas Islam Madura, 2018)
Education as instument society improvement. Clearly understanding of moral education does not only want that Indonesian come to their own morality identity. But the reduction of meaning happen in their process. Education which given must effective in order to get the social change, cleverness and freedom. The biggest failed in education for teenager is caused socials education only implement to building character, morality, attitude or thinking process of students.